2012
DOI: 10.1186/1471-2164-13-257
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide SNP scan of pooled DNA reveals nonsense mutation in FGF20 in the scaleless line of featherless chickens

Abstract: BackgroundScaleless (sc/sc) chickens carry a single recessive mutation that causes a lack of almost all body feathers, as well as foot scales and spurs, due to a failure of skin patterning during embryogenesis. This spontaneous mutant line, first described in the 1950s, has been used extensively to explore the tissue interactions involved in ectodermal appendage formation in embryonic skin. Moreover, the trait is potentially useful in tropical agriculture due to the ability of featherless chickens to tolerate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 50 publications
3
53
0
1
Order By: Relevance
“…These results are in agreement with the proposed integration of the Shh-and Bmpmediated signaling pathways in the morphogenesis (Nohno et al, 1995;Noramly and Morgan, 1998;Harris et al, 2002) and spacing (Noramly and Morgan, 1998;Bardot et al, 2004) of the placodes during feather and scale development. Similarly, Fgf signaling has been implicated in the patterning of feathers (Mandler and Neubüser, 2004;Song et al, 2004;Wells et al, 2012), and we have previously shown Fgf8 and Fgf10 to be expressed in the developing carapace of T. scripta (Loredo et al, 2001; Cebra-Thomas et al, 2005). Fig.…”
Section: Discussionsupporting
confidence: 57%
“…These results are in agreement with the proposed integration of the Shh-and Bmpmediated signaling pathways in the morphogenesis (Nohno et al, 1995;Noramly and Morgan, 1998;Harris et al, 2002) and spacing (Noramly and Morgan, 1998;Bardot et al, 2004) of the placodes during feather and scale development. Similarly, Fgf signaling has been implicated in the patterning of feathers (Mandler and Neubüser, 2004;Song et al, 2004;Wells et al, 2012), and we have previously shown Fgf8 and Fgf10 to be expressed in the developing carapace of T. scripta (Loredo et al, 2001; Cebra-Thomas et al, 2005). Fig.…”
Section: Discussionsupporting
confidence: 57%
“…Recently, it has been demonstrated that Fgf20 knockout mice do not show dermal condensation, which is required for hair follicle formation, and thus the defect results in the loss of guard hair (Huh et al, 2013). Furthermore, it has been reported that the Scaleless chicken mutant, which lacks feathers and limb scales, harbours a nonsense mutation in the Fgf20 gene (Wells et al, 2012). Moreover, the temperaturesensitive fgf20a zebrafish mutant shows gradual fin degeneration (Wills et al, 2008) and malformation of bony tissues such as the skull and scales (Cooper et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Global expression profiles reveal dynamic expression of secreted molecules in the DP during the hair cycle Rendl et al 2005;Driskell et al 2009;Greco et al 2009). Both interspecific tissue recombination experiments between epidermis and dermis and analysis of specific signaling pathways in different species have indicated that the mechanisms guiding early development of epidermal appendages are broadly conserved across taxonomic classes, including birds and mammals (Dhouailly 1973;Song et al 1996Song et al , 2004Jung et al 1998;Morgan et al 1998;Noramly and Morgan 1998;Jiang et al 1999;Noramly et al 1999;Laurikkala et al 2002;Houghton et al 2005Houghton et al , 2007Drew et al 2007;Wells et al 2012;Huh et al 2013). Thus, DP extirpation and reengraftment experiments that showed a requirement for the DP in the growth and regrowth of feathers implied a similar requirement for the DP in normal hair follicle growth and regeneration (Lillie and Wang 1941;Wang 1943).…”
Section: Dp In Development and The Hair Cyclementioning
confidence: 99%